Steal these ideas! : - Cone, Steve (The Publishing House, 2006)
Steve Cone, an advertising and marketing veteran of nearly thirty years with and for leading companies including Citigroup, American Express, Epsilon, Appple, and Fidelity, has the kind of hard-earned, high level experience that translates into valuable, tested ideas on what really works --and doesn't--in marketing. Cone delivers hundreds of pearls in a a sharp, no-nonsense, and witty style on all facets of marketing, branding, and advertising with all the candor and freshness you'd expect from a a knowledgeable good friend in the business.